Business Model Innovation in Online Preloved Fashion Enterprises - Nora Listiana (International Publisher (YAPENBI), 2026)
The growth of digital technology has encouraged the emergence of online preloved fashion enterprises as an alternative business model in the fashion industry. This sector not only addresses changing consumer behavior but also supports sustainability and circular economy practices. However, increasing competition and operational challenges require enterprises to continuously innovate their business models. This study aims to analyze business model innovation in online preloved fashion enterprises and examine its role in enhancing competitiveness and business sustainability. The research adopts a qualitative descriptive approach using literature review and case analysis of online preloved fashion businesses. The findings indicate that business model innovation, particularly in value proposition, customer engagement, digital marketing, and operational efficiency, contributes significantly to improved customer trust and market differentiation. The study concludes that continuous business model innovation is essential for online preloved fashion enterprises to achieve sustainable growth in the digital economy.